Enhancing the Capacity of Roemah Djoempoetan Srihadi SME through Socialization of Financial Risk Management Literacy - Jannah, Luluul; Pronosokodewo, Baniady Gennody; Nirbita, Betanika Nila; Norviana, Syahida; Buchori, Willa Putri Malinda (Abdi Masyarakat, 2025)
This community service initiative addresses the identified gap between theoretical understanding and practical application of financial risk management in the Roemah Djoempoetan Srihadi SME, a cultural enterprise in Yogyakarta specializing in jumputan and batik products. Despite the SME's recognized cultural value and participation in government mentoring programs, initial interviews revealed critical vulnerabilities: a complete absence of financial risk measurement, inadequate financial record-keeping, and high dependency on consignment sales models. These shortcomings render the business susceptible to capital depletion, revenue instability, and impediments to sustainable growth. The intervention employed a two-pronged methodology comprising targeted socialization sessions on financial risk management literacy and direct mentoring. The program focused on implementing practical solutions, including diversifying sales channels through e-commerce platforms, simplifying financial recording using user-friendly applications, and strengthening policy advocacy through MSME associations. The outcomes demonstrate that a comprehensive approach integrating financial literacy with strategic business adjustments significantly enhances operational resilience. This initiative underscores the necessity of transitioning culturally significant SMEs from production-centric hobbies to professionally managed enterprises, thereby ensuring the dual sustainability of both the business entity and the local cultural heritage it represents.